Conductive 2D Metal‐Organic Frameworks Decorated on Layered Double Hydroxides Nanoflower Surface for High‐Performance Supercapacitor. Issue 48 (21st December 2018) - Li, Yanli; Li, Qin; Zhao, Shihang; Chen, Chen; Zhou, Jiaojiao; Tao, Kai; Han, Lei
Abstract: The conductive two‐dimensional metal‐organic framework (Ni‐CAT) nanocones were decorated on the flower petals surface of layered double hydroxide (NiCo‐LDH) based nanoflowers, just like the surface microstructure of lotus leaves. This interesting composite structure displays excellent specific capacitance of 882 F g −1 at a current density of 1 A g −1, resulting from the synergistic between Ni‐CAT and NiCo‐LDH. An assembled asymmetric supercapacitor (ASC) using NiCo‐LDH@Ni‐CAT as positive electrode, which also diaplays high energy density of 23.5 Wh kg −1 at power density of 394.6 W kg −1 and long‐term cycling stability up to 82% after 10, 000 cycles. Therefore, this work demonstrates an excellent method of the designing and fabricating hybrid electrode materials based on conductive two‐dimensional metal‐organic frameworks and layered double hydroxides to apply in supercapacitors. Abstract : The conductive two‐dimensional metal‐organic framework (Ni‐CAT) nanocones were decorated on the flower petals surface of layered double hydroxide (NiCo‐LDH) based nanoflowers, just like the surface microstructure of lotus leaves. This interesting composite structure displays high performance as electrode material for supercapacitors.